Bacteremia With Oral in an 18-Year-Old After a Water Skiing Fall Into a Freshwater Lake - Victoria A. Avanzato DPhil; John D'Angelo MD; Jacqueline Okolie MD; Annie Massart MD (SAGE Publishing, 2023)
Freshwater exposure is associated with a diverse range of infections from pathogens present in soil and water. This includes skin and soft tissue infections and wound infections, gastrointestinal infections, and central nervous system infections acquired through recreational exposure or trauma. Case reports of freshwater-associated infections typically focus on waterborne pathogens as the cause of illness; however, patients who experience significant physical trauma during freshwater exposure may also be at increased risk for infection with their own flora if the nature of the injury allows entry of bacteria through a mechanism such as mucosal injury. Here, we present a case of a healthy 18-year-old man who rapidly developed bacteremia with oral flora following several falls submerging his face into lake water while water skiing, as well as acute polymicrobial sinusitis and subsequent pre-septal cellulitis. Shortly after his water skiing falls, the patient developed sinusitis that rapidly progressed to headaches, emesis, and significant periorbital swelling. Blood cultures grew Prevotella salivae , a bacterium naturally found in the oral cavity. Sinus cultures grew Klebsiella aerogenes and Listeria monocytogenes , which may be associated with lake water. The infection improved with antibiotic therapy, and the patient was discharged on a regimen of amoxicillin/clavulanic acid and trimethoprim-sulfamethoxazole. Reports of bacteremia with oral flora following freshwater injury are not typically reported, and to our knowledge, this is the first report describing bacteremia with P salivae .